2022
DOI: 10.1039/d1mo00411e
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics data integration approaches for precision oncology

Abstract: Next-generation sequencing (NGS) has been pivotal to enhance the molecular characterization of human malignancies, allowing multiple omics data types to be available for cancer researchers and practitioners. In this context,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 119 publications
0
5
0
Order By: Relevance
“…Understanding tumor heterogeneity, its temporal evolution over time, and the outcomes of targeted treatment are strictly dependent on accurate data collection in the context of routine clinical care 21 . In this respect, the "multi-omics" approach is gaining momentum in oncologic predictive pathology 22 . The traditional tissuebased biomarker assessment is being integrated using multiple new bioanalytes, such as blood, plasma, urines, saliva, and stool 23 , 24 , 25 , 26 biobanks and some freeware can be obtained for biobank managing 27 , 28 , 29 , 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Understanding tumor heterogeneity, its temporal evolution over time, and the outcomes of targeted treatment are strictly dependent on accurate data collection in the context of routine clinical care 21 . In this respect, the "multi-omics" approach is gaining momentum in oncologic predictive pathology 22 . The traditional tissuebased biomarker assessment is being integrated using multiple new bioanalytes, such as blood, plasma, urines, saliva, and stool 23 , 24 , 25 , 26 biobanks and some freeware can be obtained for biobank managing 27 , 28 , 29 , 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Unsupervised learning is an analytical approach that eliminates the need for prelabeled training data. The main objective of unsupervised learning is to unveil hidden patterns and establish new connections between variables within a dataset [ 107 ]. In the study of enhancers, unsupervised learning methods can be divided into distance-based methods and correlation-based methods [ 108 ].…”
Section: Multi-omics Integration Methodsmentioning
confidence: 99%
“…In supervised learning, an incorrect label definition can lead to inaccurate prediction results. Consequently, it is essential to enlist biological expertise to properly define the labels [ 107 ]. On the other hand, models, such as the ABC model and eNet model, predict the functions of thousands of enhancers.…”
Section: Challenges In Multi-omics Approachesmentioning
confidence: 99%
“…Combining multiple experimental approaches and then integrating the results is a valuable strategy to generalize human cancer’s complexity from experimental models [ 197 ]. The integration of multiple omics, such as genomics, proteomics, and metabolomics, will help us understand tumours and advance antitumor drug developments [ 198 , 199 , 200 ]. In addition, numerous studies have confirmed that developing high-throughput sequencing technologies has revolutionized multi-omics research.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%